ANALISIS METODE SERVQUAL PADA JASA PENGIRIMAN BARANG EKSPRES â€œYAKIN ESOK SAMPAIâ€ (STUDI KASUS PADA PT JNE SEMARANG) - Rachman, Mohammad; Andriyani, Andriyani (Faculty of Economics and Business Diponegoro University, 2012)
Based on data obtained from ASPERINDO that e-commerce business has significantly growing, it may boost the number of express shipments increased from year to year, Â logicly it cause good impact to JNE as well yet the fact is JNE still status quo in national scale of market share table, JNE only had 7,9% shareÂ whereas Tiki the competitor had 70,7% share on market share. The data provided ASPERINDO there would be rise a question â€why JNE and Tiki had huge gap on market share?â€ although JNE and TikiÂ established on the same year back than. Because JNE is service corporate than the study will used service approach method that is SERVQUAL (itâ€™s stand for service quality) method. This study is aimed to analyse the level of importance and performance of JNE Regional Semarangâ€™s service. Variables used in this study are service quality which consists of reliability, responsiveness, assurance, emphaty, and tangibles with the level of customer satisfaction. These variables are used to measure the Importance and Consumer Assessment of quality of services rendered the company. The research data collected data from 100 respondents of JNE customers are selected by incidental sampling through a questionnaire consisting of closed questions and opened questions. Customer Satisfaction Index is used to analyse the level of overall customer satisfaction. Meanwhile, to identify performance improvement priorities, Importance Performance Analysis method was used which consists of two components, specifically: the gap analysis (gap) and quadrant analysis. Results showed that overall customer is quite satisfied of performance of JNE express shipping service with customer satisfaction index. The application of quadrant analysis showed that indicators of dimension of reliability which should be evaluated for immediately repaired their performance, because the performance has been given not as expected by JNE customers.